The Impact of Personality and Digital Fatigue on Employee Engagement and its Implications for Job-Hopping Intention in the Hybrid Working Era at Bank Majalengka - Azzahra, Shalmalia; Kartono, Kartono (Journal Research of Social Science, Economics, and Management, 2026)
The implementation of a hybrid working system in the banking sector has increased the intensity of digital technology usage, with the potential to affect the psychological condition of employees. This condition can give rise to digital fatigue and impact employee engagement as well as job-hopping intention. Beyond technological factors, individual personality also plays a role in determining employees' responses to work demands in the hybrid working era. This study aims to analyze the influence of personality and digital fatigue on employee engagement and its implications for job-hopping intention among employees of Bank Majalengka. This study employs an associative quantitative approach with a sample of 100 Bank Majalengka employees selected using the proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using path analysis with the aid of SPSS. The results indicate that personality has a positive and significant effect on employee engagement. Personality and digital fatigue also have a positive and significant effect on job-hopping intention. However, digital fatigue does not have a significant direct effect on employee engagement, and employee engagement has not been demonstrated to mediate the influence of personality or digital fatigue on job-hopping intention. The findings of this study are expected to serve as a consideration for Bank Majalengka management in managing human resources in the hybrid working era.